Insights into the Activity Change of Spore Photoproduct Lyase Induced by Mutations at a Peripheral Glycine Residue - Yang, Linlin; Li, Lei (Frontiers in Chemistry, 2017)
UV radiation triggers the formation of 5-thyminyl-5,6-dihydrothymine, i.e. the spore photoproduct (SP), in the genomic DNA of bacterial endospores. These SPs, if not repaired in time, may lead to genome instability and cell death. SP is mainly repaired by spore photoproduct lyase (SPL) during spore outgrowth via an unprecedented protein-harbored radical transfer pathway that is composed of at least a cysteine and two tyrosine residues. This mechanism is consistent with the recently solved SPL structure that shows all three residues are located in proximity and thus able to participate in the radical transfer process during the enzyme catalysis. In contrast, an earlier in vivo mutational study identified a glycine to arginine mutation at the position 168 on the B. subtilis SPL that was later found to be > 15 Å away from the enzyme active site. This mutation appears to abolish the enzyme activity because endospores carrying this mutant were sensitive to UV light. To understand the molecular basis for this rendered enzyme activity, we constructed two SPL mutations G168A and G168R, examined their repair of dinucleotide SP TpT, and found that both mutants exhibit reduced enzyme activity. Comparing with the wildtype (WT) SPL enzyme, the G168A mutant slows down the SP TpT repair by 3~4 fold while the G168R mutant by ~ 80 fold. Both mutants exhibit a smaller apparent (DV) kinetic isotope effect (KIE) but a bigger competitive (DV/K) KIE than that by the WT SPL. Moreover, the G168R mutant also produces a large portion of the abortive repair product TpT-SO2–; the formation of which indicates that cysteine 141 is no longer well positioned as the H-donor to the thymine allylic radical intermediate. All these data imply that the mutation at the remote glycine 168 residue alters the enzyme 3D structure, subsequently reducing the SPL activity by changing the positions of the essential amino acids involved in the radical transfer process.